2016
DOI: 10.15666/aeer/1402_235251
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Composition and Diversity of Forest Along the Altitudinal Gradient in the Himalayas, Nepal

Abstract: Abstract. The aim of this study was to assess the structure (stem density, height, and basal area), composition and diversity in relatively undisturbed forests along an altitudinal gradient from 2000 m asl to 3900 m asl of Langtang National Park in Central Himalaya. The forest stands along the altitudinal gradient were studied on 20 sampling plots of two sub zones of the Temperate and Subalpine zone. Tsuga dumosa was the ecologically most important species in the Upper and the Lower Subalpine zone with high im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, the inverse J-shaped pattern documented for overall size class distribution in this study is similar to the findings of Bhutia et al [32] who found the highest number of individuals in the smallest DBH class of 3 to 13 cm and least in the highest class in Eastern Himalayan, India. This pattern is further supported by the findings of Shrestha et al [139], Dar et al [140], Pandey et al [127], and Schwab [141]. More than 90% of trees were found in lower diameter classes in the Himalayan forest of India [140].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Furthermore, the inverse J-shaped pattern documented for overall size class distribution in this study is similar to the findings of Bhutia et al [32] who found the highest number of individuals in the smallest DBH class of 3 to 13 cm and least in the highest class in Eastern Himalayan, India. This pattern is further supported by the findings of Shrestha et al [139], Dar et al [140], Pandey et al [127], and Schwab [141]. More than 90% of trees were found in lower diameter classes in the Himalayan forest of India [140].…”
Section: Discussionsupporting
confidence: 66%
“…More than 90% of trees were found in lower diameter classes in the Himalayan forest of India [140]. Pandey et al [127] recorded maximum percentages of trees in the DBH range of 10 to 29.9 cm in the trans-Himalayan region of Nepal. Most tree species in the Krummholz tree line of Rolwaling Himal, Nepal in the lower DBH range i.e., 0-14 cm were Abies spectabilis, Betula utilis, Sorbus microphylla and Rhododendron campanulatum [141].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the Eastern Himalayan forests outside of India were mainly carried out in Nepal [25,26], Bhutan [27][28][29], and China [30,31] to assess forest structure and composition. Within the Indian part of the Eastern Himalayas, studies were carried out in Arunachal Pradesh [32][33][34], Meghalaya [8,35,36], Darjeeling, West Bengal [37], and Assam [38,39].…”
Section: Past Studies In the Eastern Himalayasmentioning
confidence: 99%
“…The floristic diversity has been documented throughout the globe including India and in India all the Himalayan states like Uttarakhand, Himachal Pradesh, J&K have been covered [23][24][25][26][27]. In J&K number of studies on floristic diversity has been conducted by different workers [28][29][30][31] but the site Raithan range of Pir Panjal Forest Division, J &K, India was yet to be explored for floristic diversity and ecological study, therefore keeping in mind the importance of this study for conservation of plant ecology and sustainable utilization, this study has been conducted to assess the floristic diversity and community characteristics at different altitudes of Raithan range of Pir Panjal Forest Division, J &K, India .…”
Section: Introductionmentioning
confidence: 99%